2009
DOI: 10.1002/clc.20574
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone and Coronary Artery Disease: From Clinical Correlations to Prognostic Implications

Abstract: Background: Overt thyroid dysfunction, hypothyroidism in particular, may lead to coronary artery disease (CAD). Whether more subtle anomalies of thyroid hormone metabolism influence the progression of CAD remains a matter of speculation. Hypothesis: The occurrence of CAD and long-term prognosis in patients without a history of either primary thyroid disease, myocardial infarction, or chronic heart failure is related to serum levels of biologically active free triiodothyronine (fT3). Methods: The cohort consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 13 publications
4
48
3
1
Order By: Relevance
“…However we did not find an association between FT4 and CAD [12]. Coceani et al, studied 1047 clinically and biochemically euthyroid patients reported that serum FT3 levels were inversely correlated with the presence of CAD and the low T3 syndrome conferred an adverse prognosis, even after adjusting for the traditional coronary risk factors [13]. Coceani et al, conducted a study on 2344 patients and have recently advanced the hypothesis that low T3 exerts an adverse impact on prognosis in LV function, which is not influenced by concomitant amiodarone therapy [14].…”
Section: Limitationscontrasting
confidence: 63%
“…However we did not find an association between FT4 and CAD [12]. Coceani et al, studied 1047 clinically and biochemically euthyroid patients reported that serum FT3 levels were inversely correlated with the presence of CAD and the low T3 syndrome conferred an adverse prognosis, even after adjusting for the traditional coronary risk factors [13]. Coceani et al, conducted a study on 2344 patients and have recently advanced the hypothesis that low T3 exerts an adverse impact on prognosis in LV function, which is not influenced by concomitant amiodarone therapy [14].…”
Section: Limitationscontrasting
confidence: 63%
“…This pathological state perpetuates the deleterious cardiac remodeling and contributes to heart failure progression. In euthyroid patients with coronary artery disease, a similar pattern of low T 3 was observed and correlates with outcome [14].…”
Section: 167-8) Hamlet To Horatiomentioning
confidence: 53%
“…Experimental and clinical analyses have shown, that thyroid hormone (TH) has a fundamental role in cardiovascular homeostasis, influencing cardiac contractility, heart rate, diastolic function and systemic vascular resistance [11]. Abnormal metabolism of TH may lead to various heart diseases, like accelerated coronary atherosclerosis [12]. Coceani et al have demonstrated that free triiodothyronine (T3) levels are inversely correlated with the presence of coronary artery disease (CAD), whereas Low -triiodothyronine (T3) syndrome causes an adverse prognosis for CAD [13].…”
Section: Introductionmentioning
confidence: 99%